The effect of SCAMPER program in developing creative thinking among kindergarten children - حجه, رنا; منال سلطان; بشرى شريبة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research aimed to identify the effect of SCAMPER program in developing creative thinking among kindergarten children. In order to achieve the research objectives, the quasi-experimental approach with one group was followed based on an application on the group. The research tools were SCAMPER program and Torrance Test of Formal Creative Thinking (B). The research reached the following results: - The emergence of statistically significant differences between the average scores of the experimental group members in the pre- and post-applications on the Torrance Test of Formal Creative Thinking (B), and these differences are in favor of the post-application. - The absence of statistically significant differences between the average scores of males and females of the experimental group on the Torrance Test of Formal Creative Thinking (B). - The researcher suggested conducting more research and studies to monitor the effect of using SCAMPER program in developing creative thinking for different other age groups. And to monitor the effect of SCAMPER program in developing other types of thinking.